Analisis Tingkat Keberhasilan Kebijakan pada Program Pencegahan Perkawinan Anak - Yusroni, Ahmad; Santoso Haryono, Bambang; Nuh, Mohammad (Jurnal Ilmiah Administrasi Publik, 2024)
Child marriage is an ingrained social problem in Indonesia. The government has tried to prevent child marriage with various policies, one of which is by raising the minimum age of marriage for women to the same as men, namely 19 years, but after several years of implementation, cases of child marriage are still quite high in Indonesia. This fact is certainly very worrying, because child marriage will hamper the growth and development of children and even eliminate the basic rights that children should get such as the rights to education, health, civilian, free of discrimination and violence and other rights. Malang Regency, which contributed the highest number of child marriages in East Java in 2022, has carried out various policy programs that have succeeded in reducing the number of child marriages. This article analyzes the success of the child marriage prevention policy program in Malang District using descriptive qualitative research methods with Allan McConnell's Policy Success theory. This article explores the success of preventing child marriage from the program dimension and its level of success. The results show that in the program dimension, both the criteria for implementation according to objectives, achieving the expected results, and creating benefits for the target group fall into the Resilient Success category because behind the success of the program there are still a few discrepancies or failures in achieving goals.